Study of 46 nephrectomies in rural India - Gond, Pratik; Gangwal, Mayur; Jorwekar, Gokul J.; Wagholikar, Hrushikesh; Talreja, Ruchita (International Surgery Journal, 2021)
Background: The first planned nephrectomy was performed by the German surgeon Gustav Simon on August 2, 1869 in Heidelbergs since then nephrectomy has been an essential part of urologic practice. Elective nephrectomy is done for both benign and malignant diseases of the kidney. The objective of this study was to know the various causes their pre-op factors like age, gender, laterality of disease, and intra operative factors like duration of surgery, blood loss and post-operative complications and histopathological report of the nephrectomy specimens of elective nephrectomy in a rural medical college of India Methods: In our series, we have studied all the elective nephrectomies done in Pravara Rural Hospital, Loni during a span of three years from January 2018 to March 2021. Results: We have analyzed 46 cases of nephrectomies regarding their pre-op factors like age, gender, laterality of disease, and intra operative factors like duration of surgery, blood loss and post-operative complications and histopathological report of the nephrectomy specimens. Out of 46 cases, 21 were males and 26 females. Comparing the laterality right nephrectomy was done in 41% cases and left nephrectomy in 59% cases. In our series, 76% cases of nephrectomies were done for benign causes and 24% cases for malignant causes. Among the benign causes, pyelonephritis was the leading cause followed by neglected renal calculi and resultant non-functional kidney. On the other hand, renal cell carcinoma was the most common malignant pathology requiring nephrectomy. Conclusions: In our series, majority cases of nephrectomies were done for benign causes.